Oxidative stress and Parkinson’s disease - Blesa, Javier; Trigo-Damas, Ines; Quiroga-Varela, Anna; Jackson-Lewis, Vernice R. (Frontiers in Neuroanatomy, 2015)
Parkinson disease (PD) is a chronic, progressive neurological disease that is associated with a loss of dopaminergic neurons in the substantia nigra pars compacta of the brain. The molecular mechanisms underlying the loss of these neurons still remain elusive. Oxidative stress is thought to play an important role in dopaminergic neurotoxicity. Complex I deficiencies of the respiratory chain account for the majority of unfavorable neuronal degeneration in PD. Environmental factors, such as neurotoxins, pesticides, insecticides, dopamine (DA) itself, and genetic mutations in PD-associated proteins contribute to mitochondrial dysfunction which precedes reactive oxygen species formation. In this mini review, we give an update of the classical pathways involving these mechanisms of neurodegeneration, the biochemical and molecular events that mediate or regulate DA neuronal vulnerability, and the role of PD-related gene products in modulating cellular responses to oxidative stress in the course of the neurodegenerative process.